Handbook of deposition technologies for films and coatings science, technology, and applications - Bunshah, R. F. (Noyes Publications, 1994)
A decade after the first edition of this volume was published, this second edition is being brought out to update the many improvements in deposition technologies, its mechanisms, and applications. The entire volume has been extensively revised and contains at least 50% more material. Five chapters have been added.
Revised edition of: Deposition technologies for films and coatings, c1982.
Keywords: Coating processes.; elektronické knihy; electronic books